Pelatihan Pembuatan dan Pendampingan Penerapan Multimedia Genggam Si Dio (Camtasia Studio) Berbasis Android bagi Tutor PKBM di Kabupaten Kuningan - Dyah Puteria Wati; Dede Cahyati Sahrir; Ahmad Fajri Lutfi (Universitas Mathla'ul Anwar Banten, 2018)
TRAINING ON MAKING AND MENTORING ANDROID-BASED APPLICATION OF HANDHELD SI DIO (CAMTASIA STUDIO) MULTIMEDIA FOR PKBM TUTORS IN KUNINGAN REGENCY. Equality education of study group Package C is one of the non-formal education programs for people’s equivalent to high school level. One of the problems faced in the learning process of Package C program held by PKBM Kuningan city is not maximize the use of learning media, especially in the field of technology. This community service activity will be held in PKBM Kuningan city which already has NPSN. The purpose of this training is to improve tutor skills in making and implementing learning by utilizing android-based smartphone as a medium of learning. The method of training implementation consists of several stages: training licensing, training preparation, preparation of training module book, Si Dio handheld multimedia training, mentoring of media usage already made by tutor. Based on the results of training and mentoring the application of handheld multimedia Si Dio based on android this can help improve and improve the quality of the process of Package C equivalence program and facilitate understanding even though learners learn independently.